THE ROLE OF CULTURE IN LEARNING FOREIGN LANGUAGES - Ergasheva Xayriniso Abdurasul qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Language and culture are intertwined in human existence, particularly in learning and language education. The purpose of this research is to describe cultural understanding in English learning. This study is classified as qualitative research since the data was gathered through library research. This culture is highly appropriate for foreign language study, which focuses on improving communication skills with the target language. The incorporation of culture into the English learning process might lessen the likelihood of misconceptions occurring throughout the communication process.